Cultural Tourism in the Recôncavo Region (State of Bahia): panorama of the organizations of Cachoeira, Bahia, Brazil - Queiroz, Lúcia Maria Aquino de; Faria, Diomira Maria Cicci Pinto (Revista Turismo em Análise, 2019)
This article aims to analyze cultural tourism organizations in the city of Cachoeira, located in Recôncavo Baiano. Understanding the complexity involved in the development of tourism and believing that territories, their social actors and organizations must be able to conceive and promote forms of tourism that best meet their needs and development goals, it seeks to deepen knowledge about a fundamental resource for success of cultural tourism in a given destination: local organizations directed to the activity. In methodological terms, it investigates the profile, challenges, assessments and partnerships held by the organizations of Cachoeira, using the “Snowball” technique, in which, successively, an actor indicates another participant. Then, through the Social Network Analysis, it maps the dynamics of these relationships in a given period of time. Observes, through the surveys carried out, that in Brazil, even in national heritage cities, cultural tourism is not perceived and treated as a priority by local managers and, in general, public administrations still need to support this activity more intensely. It understands that, through the increase of the actions in partnership, organizations and social actors can be strengthened and reach greater protagonism in the decisions that permeate the activity, this being a possible way for the tourism to expand bringing a greater contribution to the development of urban spaces in Brazil.